Interface-Based Loan Fund Performance Monitoring And Evaluation System At BKM Ngesrep Semarang - Lilis SuryanI; Danang Danang; Khoirur Rozikin (Journal of Engineering, Electrical and Informatics, 2023)
The monitoring and evaluation system is a routine process of collecting data and measuring progress on program objectives/monitoring changes, which focuses on processes and outputs. Monitoring involves accounting for what is done. Monitoring involves observing the quality of the services provided while evaluation is the use of social research methods to systematically investigate program effectiveness/assess the program's contribution to change (goal/objective) and assess the need for improvement, continuation or expansion of the program (recommendations). The first aim of this system is to be able to process data efficiently and accurately, the second aim is to assist the financial management unit (UPK) in inputting loan fund installments to make it easier to process data so as not to make calculation errors and record errors and to improve services to Community Self-Help Groups (KSM) better as borrowers, the third objective is to facilitate monitoring of loan fund evaluation which can be monitored and evaluated at any time, both the rate of return of loan funds and the level of loan fund congestion. In this system, the interface-based monitoring and evaluation model is one of the services provided by the operating system as a means of interaction between the user and the operating system. The interface is an operating system component that comes into direct contact with the user. This application was created using Microsoft Visual Basic 6.0 and a Client Server-based MySQL database.